2019
DOI: 10.1111/jnc.14912
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of constitutive proteasomes in experimental autoimmune encephalomyelitis may be caused by a combination of subunit displacement and reduced Nfe2l1 expression

Abstract: The goal of this study was to determine if subunit displacement and/or alterations in proteasome biosynthesis could explain the changes observed in the levels of constitutive proteasomes (c‐20S) and immunoproteasomes (i‐20S) in the spinal cords of mice with experimental autoimmune encephalomyelitis (EAE). To this end, EAE was induced in C57BL/6 mice by immunization with MOG35–55 peptide. Spinal cords were collected at different times during the disease course and used for western blotting, RNA analysis, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…NFE2L1 and its paralog NFE2L3 maintain the basal proteasome activity, while the simultaneous deletion of those proteins impairs proteasome function in cancer (39,63). Acting through the downregulation of NFE2L1, autoimmune inflammation induces t h e p r o t e a s o m e s u b u n i t d i s p l a c e m e n t f o r m i n g t h e immunoproteasome (64). In this study, we found that the experimental hypoxia suppressed the mRNA levels of NFE2L1 and let IFNg activate the transcription of the proteasome subunits in CD14 + cells, while the exposure to JAKi upregulated NFE2L1, which decreased immunoproteasome production.…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L1 and its paralog NFE2L3 maintain the basal proteasome activity, while the simultaneous deletion of those proteins impairs proteasome function in cancer (39,63). Acting through the downregulation of NFE2L1, autoimmune inflammation induces t h e p r o t e a s o m e s u b u n i t d i s p l a c e m e n t f o r m i n g t h e immunoproteasome (64). In this study, we found that the experimental hypoxia suppressed the mRNA levels of NFE2L1 and let IFNg activate the transcription of the proteasome subunits in CD14 + cells, while the exposure to JAKi upregulated NFE2L1, which decreased immunoproteasome production.…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L1 and its paralog NFE2L3 maintain the basal proteasome activity, while simultaneous deletion of those proteins impairs proteasome function in cancer cells 39,63 . Acting through down-regulation of NFE2L1, autoimmune inflammation has been shown to trigger the subunit displacement in S26 proteasome complex forming the immunoproteasome 64 . Indeed, we found that experimental hypoxia suppressed mRNA levels of NFE2L1 in CD14 + cells having no significant effect on the metabolic signature.…”
Section: Discussionmentioning
confidence: 99%
“…In animal model, experimental autoimmune encephalomyelitis (EAE) is widely used for autoimmune disorders of the central nervous system, particularly multiple sclerosis, in which proteasomal types show two distinctive and even opposite responses: constitutive proteasome (i.e., c-proteasome) levels decrease, while immunoproteasome (i.e., i-proteasome) levels rise [ 90 , 91 ]. A study by Shanley et al suggests that the changes in c-proteasome may be just due to reduced expression of NFE2L1, but their subsequent work further showed that this reduction is likely not attributable to pro-inflammatory cytokine exposure [ 91 , 92 ]. However, the exact cause of this effect remains unknown to date, although it may be quite informative to assess if reversing NFE2L1-lowered levels could negate the phenotype of EAE.…”
Section: Grievous Consequences Of Nfe2l1 Disruptio...mentioning
confidence: 99%